Menuju Urbanisasi Pulau Kecil: Produksi Ruang Abstrak dan Perampasan - Yoppie Christian; Desmiwati Desmiwati (P4W LPPM IPB, 2018)
Agrarian conflict in Pari Island of Seribu Islands, Jakarta has been undergoing for more than twenty years. The conflict involves main parties, in which the locals are diametrically opposed to local government-backed tourist corporations. This inductive qualitative study explores the historical information of the conflict and constructs a theoretical proposition at the mezzo level concerning the cause of this conflict by using an analytical tool from Lefebvre's concept of